The Agrarian Tale of Kenderan Village: Sarcophagus, a Magical Priest, and Farming Sciences - Ida Bagus Putra Setiawan (Bali Tourism Board, 2021)
In discussing Bali’s agricultural history development, the name of Kenderan village would occasionally appear. It is one of many villages that inherited subak tradition from ancient times. The town, located in Tegalalang district, Gianyar, has witnessed the growth of farming customs on the island of the gods. The people of the kenderan village have been an agricultural society since the megalithic period around 4500–1500 BC. It is proved by the Sarcophagus around the village and the bronze nekara printing similar to Nekara in Pejeng. These remnants signed that there was a settlement with high cultural society. Nekara was used as a drum to summon rain related to agricultural practice. Further, after Padanda Sakti Manuaba’s arrival, the society was introduced to a water reservoir system, dam, and rituals needed to support the farm’s sustainability. The community keeps the tradition and rituals as part of their identity up to the moment. Every year, through a distinctive ritual, ‘nyawang,’ they express their gratitude to God for a long, lush, fertile and prosperous life.